(untitled) (Research, Society and Development, 2022)
The objective of this study was to describe and analyze breast cancer morbimortality in different Brazilian regions, through the analysis of absolute numbers and hospitalization and mortality rates. For this, it was an ecological, retrospective study, of a descriptive nature, with a quantitative approach, using data obtained through access to the electronic address of the Department of Informatics of SUS/DATASUS. The target population consisted of women residing in Brazil, with Malignant Breast Neoplasia, aged 30 years or older, identified by means of registration in the Death Certificate and Declaration of Internment, from fill the Hospitalization Authorization Hospitalar - HAA, which took place between 2017 and 2021. The main findings reveal that compared to other regions of the country, the North region has the highest mortality rate (9.52%) and the lowest hospitalization rate (35.36%) in the studied period, in contrast to the South region, which had the highest hospitalization rate (82.27%) and the lowest mortality rate (7.48%) in the same period. Finally, the relevance of knowledge about risk factors, prevention and early diagnosis is reiterated, as well as the need for interregional epidemiological analyzes on breast cancer in order to support the planning, implementation and evaluation of public policies focused on this disease.